Circularly Polarized Luminescence and a Reflective Photoluminescent Chiral Nematic Liquid Crystal Display Based on an Aggregation‐Induced Emission Luminogen. Issue 4 (8th January 2016) - Zhao, Dongyu; He, Hexiang; Gu, Xinggui; Guo, Lin; Wong, Kam Sing; Lam, Jacky W. Y.; Tang, Ben Zhong
Abstract : A reflective photoluminescent liquid crystal (LC) display device that can work under both sunlight and UV light irradiation is reported. This device is based on photoluminescent chiral nematic liquid crystals that combine selective reflection and circularly polarized luminescence. The reflective luminescent LC display provides promising prospects for future energy‐saving displays under different lighting conditions.